Central 5-HT receptors and their function; present and future. (15th October 2020) - Sharp, Trevor; Barnes, Nicholas M.
Abstract: Since our review of central 5-HT receptors and their function twenty years ago, no new 5-HT receptor has been discovered and there is little evidence that this situation will change in the near future. Nevertheless, over this time significant progress has been made in our understanding of the properties of these receptors and in the clinical translation of this information, and some of these developments are highlighted herein. Such highlights include extensive mapping of 5-HT receptors in both animal and human brain, culminating in readily-accessible brain atlases of 5-HT receptor distribution, as well as emerging data on how 5-HT receptors are distributed within complex neural circuits. Also, a range of important pharmacological and genetic tools have been developed that allow selective 5-HT receptor manipulation, in cells through to whole organism models. Moreover, unexpected complexity in 5-HT receptor function has been identified including agonist-dependent signalling that goes beyond the pharmacology of canonical 5-HT receptor signalling pathways set down in the 1980s and 1990s. This new knowledge of 5-HT signalling has been extended by the discovery of combined signalling of 5-HT and co-released neurotransmitters, especially glutamate. Another important advance has been the progression of a large number of 5-HT ligands through to experimental medicine studies and clinical trials, and some such agents have already become prescribed therapeutic drugs. Much more needs to be discovered and understood by 5-HT neuropharmacologists, not least how the diverse signalling effects of so many 5-HT receptor types interact with complex neural circuits to generate neurophysiological changes which ultimately lead to altered cognitions and behaviour. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: Highlights developments in non-canonical 5-HT receptor signalling, and biased agonism. Reviews 5-HT receptor mapping and cellular distribution. Highlights pharmacological tools for 5-HT receptor manipulation. Reviews behavioural and cognitive effects of 5-HT receptor manipulation. Highlights progression of 5-HT ligands from preclinical to clinical investigation.